Cover Picture: Plasma Process. Polym. 2∕2016. Issue 2 (February 2016) - Alcaire, Maria; Filippin, Alejandro Nicolas; Macias‐Montero, Manuel; Sanchez‐Valencia, Juan R.; Rojas, Teresa Cristina; Mora‐Boza, Ana; Lopez‐Santos, Carmen; Espinos, Juan P.; Barranco, Angel; Borras, Ana
Abstract : Front Cover: Nowadays, highly porous ZnO materials play a key role as nanosensors, solar cells, photonics devices and photo‐catalysts. The protocol developed in this work combines physical vapour deposition and remote plasma etching using Zn‐phthalocyanine as vacuum processable precursor for foam‐like layers and 1D nanostructures. The methodology for the fabrication of ZnO nanostructures is straightforwardly extensible to an ample range of porous metal oxides just selecting the metal‐phthalocyanine/porphyrin sublimable precursors. Further details can be found in the article by Maria Alcaire et al.on page 287 .